Histories of punishment and social control in Ireland : perspectives from a periphery - Black, Lynsey; Brangan, Louise; Healy, Deirdre (Perspectives on crime, law and justice in the global south, 2022)
This volume contains an Open Access Chapter As a peripheral state within English-speaking criminology, Ireland is often overlooked in mainstream Anglophone theories of punitiveness and penal transformation. This edited collection addresses this deficit by bringing together leading scholars on Irish penal history and theory to make a case for Ireland's wider theoretical relevance. Together, these chapters show in rich detail the trends and debates that have surround patterns of punishment in Ireland since the formation of the State in 1922. However, by being about twentieth century Irish penal history, the volume inherently foregrounds often absent perspectives in criminology and punishment, such as gender, postcoloniality, religion, rurality, and carcerality beyond the criminal justice system. This is more than a collection of Irish criminology, therefore; the social analysis of Irish penal history is undertaken as a contribution towards southernising criminology. The authors each seek to engage criminology in a wider epistemological re-imagining of what is meant by punitiveness, penal culture, and 'Anglophone' penal history. Opening up new avenues of exploration and collaboration, and showing how researchers might look beyond the usual problems, refine the mainstream trends, and rework the obvious questions, this collection demonstrates how the Irish perspective remains relevant for international researchers interested in punishment and history.